Pendekatan Modal Sosial Sebagai Resolusi Konflik Desa Laju Vs Desa Tolouwi Kabupaten Bima - Firdaus; Oman Sukmana; Vina Salviana (Syntax Idea)
Laju Village has been recognized as a conflict-prone area due to various past social conflicts, including a major conflict with Tolouwi Village. This conflict not only caused significant financial losses but also resulted in casualties, making it the most serious incident compared to previous conflicts. In this context, understanding conflict resolution mechanisms is crucial for maintaining social stability in the region. This study aims to analyze the role of social capital in resolving conflicts between Laju Village and Tolouwi Village. The research employs a qualitative approach, with research subjects consisting of key stakeholders, such as community leaders and government officials. The object of the study focuses on the conflict resolution mechanisms applied in social interactions between the two villages. Data were collected from primary and secondary sources to provide a comprehensive understanding of conflict dynamics and resolution efforts. The findings indicate that the conflict between Laju Village and Tolouwi Village can be resolved through the utilization of social capital embedded within the community. This social capital includes social institutions, mutual trust, and established social networks. Furthermore, strong relationships fostered through various social and economic activities, such as agriculture, livestock farming, business, and kinship ties formed through intermarriage, have proven to be key factors in achieving peace and reconciliation. The implications of this study emphasize that social capital can serve as an effective instrument in mitigating conflicts and strengthening social harmony in rural communities. Therefore, efforts to enhance social networks and build trust among community members should be continuously pursued as a preventive strategy against potential future conflicts.